Determining the distribution and genetic diversity of Coguvirus eburi in South African citrus and development of a citrus-infecting coguvirus detection assay - De Bruyn, Rochelle (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.